Humor and Wisdom (Content Analysis of Dakwah by Das'ad Latif on Instagram) - Alfauzie, Risaldi; Husain, Wahyuni; A, Aswan; Mahmud, Adilah (State Islamic Institute of Bone, Indonesia, 2023)
This research aims to determine (1) Das'ad Latif's profile, (2) humor in Dakwah by Das'ad Latif on Instagram, and (3) wisdom in Dakwah by Das'ad Latif on Instagram. This study utilizes content analysis with a descriptive technique and a qualitative approach. To collect data, the researcher employed observation and documentation methods. The results of this study indicate that Das'ad Latif frequently discusses women in his Dakwah due to their occasional inability to maintain proper behavior and morals, which should govern their conduct. On his Instagram account, humorous Dakwah messages containing morals were found, consisting of 5 messages, including morals towards others, morals towards parents, and morals towards partners. In these humorous Dakwah messages, there were 3 Dakwah videos discussing women: